Corrosion Study on X65 Steel with Wax Deposition under Thermal Effect - Haji Rosihan, Siti Salmiah (IRC, 2016)
Flow assurance and corrosion have become the major challenges that greatly impact the oil and gas industry. The presence paraffin wax causes wax deposition that leads to pipe blockage while the corrosion attack of dissolved CO2 gas can impair the integrity of the pipeline. Studies proved that precipitated wax on steel can act as a natural barrier to corrosion attack but the wax is sensitive to temperature especially when the fluids in the pipe increase above wax appearance temperature (WAT),. Therefore, the objectives of this project are to design and develop a modified cold spot method to simulate the wax deposition on steel sample via laboratory experiment and to study the effect of temperature and time on the corrosion behaviour of the specimens.